Optimal mix of policy instruments and green technology transitions - Prudence Dato; Frank C. Krysiak (University of Basel, Center of Business and Economics (WWZ), 2021)
Green innovation is a key element in fighting climate change. But there are several challenges that need to be addressed in managing a green technology transition, both in terms of interacting market failures (environmental externality, public good nature of innovation, strategic behaviour of incumbents protecting an emission-intensive technology) and as the structure of the technology market (whether the new technology is offered by a monopolistic incumbent or whether there is some competition induced by market entrants) will evolve throughout the transition. In this paper, we investigate the question what constitutes the optimal policy at different stages of the technology transition and for different market structures. We first analyse a policy mix that can implement a first-best outcome. We show that this mix will differ between different market settings and for different stages of the technology transition. Second, we investigate the choice between a push policy (subsidy for the new technology) and a pull strategy (tax on the old technology) and show that throughout the transition, the policy should be switched, often even more than once. Overall, our results indicate that managing a green technology transition requires a sequence of different policies attuned to the state of the transition and that this sequence differs substantially for different cases, for example, different levels of environmental damage or different cost advantages of the incumbent over entrants.
Keywords: 330; Policy; Tax; Subsidy; Green Technology; Imperfect Competition; Technology Transition